2003
DOI: 10.1111/j.1525-1438.2003.13364.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of anthracyclines in second-line therapy of ovarian cancer

Abstract: Anthracyclines (ANTs) have been in clinical practice since the 1960s and represent one of the most commonly used classes of anticancer drugs. In the 1990s, meta-analyses showed a favorable impact of doxorubicin (DOX/A) on the survival of patients with advanced ovarian cancer, when it was combined with cyclophosphamide and cisplatin (CAP) and compared to CP alone. With the acceptance of paclitaxel-carboplatin (TCb) as the new reference arm for first-line treatment, testing the addition of ANTs to TCb seems a lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 36 publications
(54 reference statements)
0
13
0
Order By: Relevance
“…Other trials that are ongoing will provide further evidence on any added benefits of anthracyclines. 19 The comparison of survival curves across different experiments requires knowledge of prognostic factors for individual patients in both experiments. 20 Indeed, as shown in Fig 3, the expected survival curve depends heavily on the prognostic factors found to be significant in the survival model for advanced ovarian cancer (extent of residual disease, age, FIGO stage, and histologic grade).…”
Section: Discussionmentioning
confidence: 99%
“…Other trials that are ongoing will provide further evidence on any added benefits of anthracyclines. 19 The comparison of survival curves across different experiments requires knowledge of prognostic factors for individual patients in both experiments. 20 Indeed, as shown in Fig 3, the expected survival curve depends heavily on the prognostic factors found to be significant in the survival model for advanced ovarian cancer (extent of residual disease, age, FIGO stage, and histologic grade).…”
Section: Discussionmentioning
confidence: 99%
“…Anthracycline antibiotics are among the most important antitumour agents and have been in clinical practice since the 1960's. The fi rst generation anthracyclines, doxorubicin and daunorubicin, are produced by some Streptomyces species (Vermorken et al, 1999). Although epirubicin differs from doxorubicin only in the orientation of the 4'-hydroxy group, this minor difference has important consequences on the spectrum of their activity (Minotti et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…It has been approved by Food and Drug Administration (FDA, 2000). Epirubicin has been used extensively in the treatment of a wide range of cancers, including breast, ovarian, gastric, bladder, and colorectal carcinomas, lymphomas, leukemias, and multiple myelomas (Cersosimo and Hong, 1986;Muggia and Green, 1991;Coukell and Faulds, 1997;Vermorken et al, 1999). It is used alone or in combination with other drugs.…”
Section: Introductionmentioning
confidence: 99%
“…In a review analysis, Vermorken et al (1999) showed that 25 out of 75 (33%) chemotherapy patients from several trials achieved an objective response to single agent doxorubicin. The results of single agent epirubicin appear to be better in prior platinumexposed patients.…”
mentioning
confidence: 99%